2018
DOI: 10.1101/348466
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-invasive prenatal testing as a valuable source of population specific allelic frequencies

Abstract: Low-coverage massively parallel genome sequencing for non-invasive prenatal testing (NIPT) of common aneuploidies is one of the most rapidly adopted and relatively low-cost DNA tests. Since aggregation of reads from a large number of samples allows overcoming the problems of extremely low coverage of individual samples, we describe the possible re-use of the data generated during NIPT testing for genome scale population specific frequency determination of small DNA variants, requiring no additional costs excep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 22 publications
(20 reference statements)
0
19
0
Order By: Relevance
“…Although the sequencing depth per sample was low, there might be more than one read from the same sample overlapping at a genome position. This problem may affect the estimation of allele frequency because the estimation is based on the assumption that a sample may contribute only 0 or 1 allele (read) at any given genome position [12,13]. For instance, we found that the average percentage of genome positions with depth 2x (i.e.…”
Section: Genome Coverage and Sequencing Depth Of The Nipt Datasetmentioning
confidence: 97%
See 4 more Smart Citations
“…Although the sequencing depth per sample was low, there might be more than one read from the same sample overlapping at a genome position. This problem may affect the estimation of allele frequency because the estimation is based on the assumption that a sample may contribute only 0 or 1 allele (read) at any given genome position [12,13]. For instance, we found that the average percentage of genome positions with depth 2x (i.e.…”
Section: Genome Coverage and Sequencing Depth Of The Nipt Datasetmentioning
confidence: 97%
“…At any genome position, there were on average 47 out of 2,683 samples that each contributed two reads (Supplementary Figure S3). To address this problem, we followed a filtering strategy from previous studies [12,13] to keep only one read if there were overlapping reads in a sample. Thus, for every genome position, each sample could only contribute up to one read, and when the samples were aggregated, all reads at any position were obtained from different samples.…”
Section: Genome Coverage and Sequencing Depth Of The Nipt Datasetmentioning
confidence: 99%
See 3 more Smart Citations